2007
DOI: 10.1080/17476930601140343
|View full text |Cite
|
Sign up to set email alerts
|

On explicitly solvable Vekua equations and explicit solution of the stationary Schrödinger equation and of the equationdiv(σ∇u)=0

Abstract: We consider the known classes of explicitly solvable Vekua equations and construct new ones. Using the relationship between the Vekua equations and second order equations we obtain explicitly solvable stationary Schro¨dinger equations as well as explicit solutions for the equation divðruÞ ¼ 0, when is an even positive or negative power of an arbitrary harmonic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 10 publications
0
30
0
Order By: Relevance
“…In the case of a real valued function f the relation between solutions of (18) and equations (20), (21) was observed in [20], and between solutions of (18) and equations (22), (23) in [18].…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of a real valued function f the relation between solutions of (18) and equations (20), (21) was observed in [20], and between solutions of (18) and equations (22), (23) in [18].…”
Section: Preliminariesmentioning
confidence: 99%
“…Hence from the just proven equation (20) we obtain that W 1 is a solution of (22). In order to obtain equation (23) for W 2 it should be noted that…”
Section: Preliminariesmentioning
confidence: 99%
“…p-analytic functions found numerous applications in elasticity theory (see, e.g., [1,11,13]), in problems of fluid dynamics (see, e.g., [9,10,23,24,30]). The system describing p-analytic functions is closely related to the stationary Schrödinger equation and the conductivity equation [5,14,15,17,19,20]. One of the most important and intensely studied classes of p-analytic functions are x kanalytic functions, where k is any integer number (see, e.g., [1,6,9,12,21,22,25,29,30]).…”
Section: Introductionmentioning
confidence: 99%
“…TWO-DIMENSIONAL CASE: PSEUDOANALYTIC APPROACH As it was explained in [17], recent discoveries in the theory of pseudoanalytic functions [11] has shown that equation (1), for the two-dimensional case, is completely equivalent to a special Vekua equation of the form…”
mentioning
confidence: 99%
“…The correspondence between W 1 and W 2 is one to one. Proposition 3: [11] Let W = W 1 + iW 2 be a solution of (9). Then the function…”
mentioning
confidence: 99%